Innovative Leadership Behavior for Developing National Education Standards - Maharani Wicahyaningtyas; Binti Maunah; Abd. Aziz (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
Educational institutions are increasingly required to respond to rapid educational reforms, technological advancement, and rising expectations for educational quality, making innovative leadership an essential competency for school principals. However, limited empirical research has examined how innovative leadership behavior contributes to the development of the National Education Standards (Standar Nasional Pendidikan) within Islamic educational institutions. This study aims to analyze the innovative leadership behavior of madrasah principals in developing the National Education Standards through a multisite qualitative study conducted at MTs Negeri 3 Jombang and MTs Negeri 16 Jombang, Indonesia. A qualitative multisite case study design was employed, involving principals, vice principals, teachers, administrative staff, school committee members, and supervisors selected through purposive sampling. Data were collected through in-depth interviews, non-participant observations, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldaña, followed by within-site and cross-site analysis. The findings reveal that innovative leadership behavior operates through four interconnected stages: opportunity exploration, idea generation, idea championing, and idea implementation. These behavioral stages enable principals to transform educational challenges into sustainable institutional innovation through collaborative planning, stakeholder engagement, resource mobilization, and continuous evaluation. The study proposes an Innovative Leadership Behavior Model for Madrasah Development, extending the Innovative Work Behavior framework into educational leadership. The findings contribute to the literature on educational leadership by providing a behavioral perspective for understanding sustainable school improvement and offer practical implications for strengthening leadership capacity in implementing the National Education Standards within Islamic educational institutions